Influence of Mountain Wildfires on the Insulation Properties of Air Gaps in Power Grids - Fangrong Zhou; Hao Geng; Gang Wen; Yutang Ma; Yi Ma; Guofang Wang; Jun Cao; Jiaze Xu; Hongwei Mei (Energies)
The complex terrain of China frequently leads to wildfires, which in turn pose a threat to the safe operation of power transmission lines. Studying the breakdown characteristics of air gaps under wildfire conditions is of great significance for understanding wildfire propagation mechanisms, risk assessment and management, and ecological environment protection. This paper establishes an experimental platform simulating wildfire climatic conditions and conducts experimental research on air gaps between rod–rod gaps and conductor–ground gaps. The experimental voltage types include direct current, power frequency, and standard operating waves. The impact of wildfire factors on the breakdown voltage and discharge characteristics of air gaps was obtained. The results indicate that the main factors affecting the air gap breakdown characteristics during wildfires are flame height and smoke. Flame height directly influences the gap insulation distance. Under flame bridging conditions, the maximum decrease in breakdown voltage reaches 70–80%. As the concentration of smoke increases, the degradation of insulation performance becomes more pronounced, with a reduction ranging from 20% to over 50%.